THE DEVELOPMENT OF QUIZIZZ LEARNING MEDIA TO IMPROVE LISTENING SKILLS IN 5TH GRADE ON THE SOCIAL SCIENCES LEARNING - Fitriyani, Fitriyani; MS, Zulela; Edwita, Edwita; Yarmi, Gusti; Rokmanah, Siti (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
AbstrakThe purpose of this research is to improve students’ listening skills during the learning process by developing a product in the form of Quizizz learning media. This research was conducted on 5th grade elementary school students with 56 students as respondents. This research is a type of research and development (R&D) with the Borg and Gall model. Before developing a product, the needs analysis, literature review, observation, interviews, questionnaires, tests, and documentation were carried out. The preliminary study results stated that the Quizizz learning media was very much needed in Social Science learning. The evaluation process is conducted in 3 stages, 1) expert judgment by linguists and media. 2) a one-to-one evaluation is conducted with 3 students who have high, medium, and low abilities. 3) evaluate a small group (20 students). The test results express that the Quizizz learning media is feasible to use. To see the effectiveness of the product and improve listening skills, it was followed by a field group test with 33 students. The results of the t-test analysis show the different improvements in listening skills between the pretest and post-test. The average score indicates that the Quizizz learning media developed is effectively used in Social Science learning and can improve the listening skills of students.Keywords: Social Science; Learning Media; Listening Skills